Tingkat Stres Ibu Muda di Masa Pandemi Covid-19: Bagaimana Peran Resiliensi dan Sikap Sabar? - Medina Chodijah (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2021)
This study aims to examine the role of resilience and patience on stress level experienced by young mothers during Covid-19 pandemic. This study is a quantitative correlational research using 3 instruments in a set of questionnaire that is: resilience and patience questionnaire developed by the researcher, and Pandemic-Related Perceived Stress Scale of Covid-19 (PRPSSC) developed by Campo-Arias and colleagues. The participants were 44 young mothers who have 1st- and 2nd-grader children in Pasirbitung village, Tasikmalaya. The results show that most of the participants have resilience (70.4%) and patience (88.6%) in high level, and stress in mild level (70.5%). Resilience and patience have negative effect on stress level of the mothers. That is, the higher resilience and patience, the lower stress experienced by the mothers.